The demand for euro banknotes issued in Germany: Structural modelling and forecasting - Nikolaus Bartzsch; Franz Seitz; Ralph Setzer (Research On Money in the Economy (ROME), 2015)
This paper explains and forecasts the demand for banknotes issued in Germany. For small and large denomination notes we estimate vector error correction models (VECM). The results suggest that the long-run demand for German small denomination notes is mainly driven by domestic transactions and demand from outside the euro area. The transaction motive in the rest of the euro area is part of the short-term dynamics. The long-run demand for German large denomination notes is mainly driven by foreign demand both from the rest of the euro area and outside the EMU. The global financial crisis led to a one-time increase in the (real) demand for these notes. Our results are in line with estimates according to which the level and dynamics of banknote demand are mainly determined by foreign demand. Additionally, we present RegARIMA models for the medium denominations as it was not possible to build a VECM for these denominations.
Keywords: C22; C32; E41; 330; banknotes; vector error correction; RegARIMA; forecasts